The Rockefeller Foundation and the Training of Agricultural Specialists for Latin America: a Profile of Scholars from Latin American Scholarship Program in Agriculture (1951-1962) - M. Heinz, Flavio; Korndörfer, Ana Paula; de Brum, Cristiano Enrique (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2022)
Between 1951 and 1962, the Rockefeller Foundation (RF) maintained a scholarship program, the Latin American Scholarships program in agriculture (LAS), which financed the training of 226 Latin American students and researchers who, together, received 297 scholarships for short study periods at leading research centers in countries in the region. These centers were, above all, structures linked to the Office of Special Studies (OSS), a partnership between the Rockefeller Foundation and the Mexican government, and North American universities. The LAS provided the training and circulation of Latin American scholars in a period of great technological advancement in agricultural research and sought to give continental scope to RF’s main and most successful laboratory in the area: Mexico. The profile analysis of 226 LAS scholars is made from a database of 9057 minibiographies of scholars available in the Directory of Fellowships and Scholarships published by the Rockefeller Foundation in the 1970s.